Turbulent flow field comparison and related suitability for fish passage of a standard and a simplified low‐gradient vertical slot fishway. (25th August 2017) - Quaranta, E.; Katopodis, C.; Revelli, R.; Comoglio, C.
Abstract: Fishways are hydraulic structures that allow passage of fish across obstructions in rivers. Vertical slot fishways—VSFs—are considered the most efficient and least selective type of technical fishway solutions, especially due to their ability to remain effective even when significant upstream and/or downstream water level fluctuations occur. The scope of the present study is to perform numerical simulations in order to investigate and compare the hydraulic turbulent flow field in a standard and a simplified version of the most common VSF design. Implications in relation to fish swimming behaviour and fish passage performance are discussed. Different water depths (as well as discharges) were investigated, using a bed slope of 5%, as a reference for low‐gradient VSFs with a very limited selectivity that can be used in multispecies rivers in grayling‐barbel regions. Results show that maximum values of velocity, turbulent kinetic energy, and Reynolds stresses are higher in the standard design. However, corresponding to slot geometry and orientation, the direction of the main jet in the simplified design is more inclined towards the left side of the pool. This causes the eddy to split into 2 smaller ones; the minimum eddy dimension is reduced from 0.4–0.5 to 0.2–0.3 m. These dimensions are detrimental for fish passage efficiency, being more comparable with fish length (0.15–0.40 m), thus affecting migrating fish stability and orientation. Furthermore, the standard design provides a more straightforward upstream path and wider areas of low flow velocities and turbulence, useful for fish resting. Therefore, it is recommended that the standard design should be preferred over its simplified version, even if its construction costs are around 10–15% higher than the simplified one.